IMPLEMENTASI PROGRAM LITERASI MELALAUI PENDEKATAN MEANINGFULLEARNING PADA PEMBELAJARAN AKIDAH AKHLAQ DALAM MEMBENTUK KARAKTER SISWA KELAS XII MA DARUT TAQWA PURWOSARI PASURUAN - Putri Febryanti, Fanny; Ahmad Marzuki; Yusuf, Achmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The background of this study is based on the importance of literacy as a means to strengthen religious understanding while fostering students' character amid an era that demands critical and reflective thinking. This study examines the implementation of a literacy program using a meaningful learning approach in Akidah Akhlak instruction to develop the character of twelfth-grade students at MA Darut Taqwa Purwosari Pasuruan. The study aims to describe the implementation of the literacy program through the meaningful learning approach in Akidah Akhlak instruction and to analyze the program's implications for shaping students' character. The method used is qualitative research of the case study type. Data were collected through observation, interviews, and documentation, then analyzed through the stages of data reduction, data display, and conclusion drawing. The results indicate that implementing a literacy program based on meaningful learning in Akidah Akhlak realized through a series of reflective writing activities and retellings of the stories of the four madhhab imams proved effective not only in deepening students' understanding of doctrinal concepts but also in shaping consistent religious character, enhancing students' ability to cooperate, instilling disciplined learning habits, and encouraging the courage to express opinions and take initiative in the learning context. The integration of the literacy program with the meaningful learning approach made Akidah Akhlak instruction more meaningful, active, and relevant to students' life contexts, enabling the values of creed and moral conduct to take root within them. Thus, the literacy program not only improves reading and text-comprehension skills but also supports the formation of religious character, discipline, responsibility, and noble moral conduct.